THE EFFECTS OF PARENTAL READING SOCIALISATION ON THE READING SKILL PERFORMANCE OF RURAL PRIMARY SCHOOL STUDENTS IN SARAWAK - Humaira, Raslie; Radina, Mohamad Deli; Dexter Sigan, John; Damien, Mikeng; Ambigapathy, Pandian (AESS Publication, 2020)
Extant research on home literacy practices such as parental reading socialisation have demonstrated positive impacts on children in terms of academic performance. A particular aspect that sparks pedagogic importance is the scaffolding potential of reading at home to the learning of English language in non-native English Language contexts. This study aimed to examine the effects of mother’s involvement in home-reading sessions on students’ English reading skill performance in Bau, Sarawak. Prior to carrying out the intervention of reading at home with their children, 31 mothers of Bidayuh ethnicity voluntarily attended a one-day workshop to orient them to the intervention and the use of logbooks to record details of their shared readings. However, only 18 mothers conducted reading sessions with their children and submitted a total of 21 logbooks detailing the frequency and material selection for reading. Their children, consisting of primary 1 to 4 students were required to sit for a pre-test and a post-test that measure their English language reading proficiency. The test scores were analysed using the paired-sample T-test. There was a significant increase in the students’ post-test scores following the reading intervention. The results revealed that despite the low frequency of mother-child shared reading sessions, the sessions positively affected the students’ reading performance. This finding suggests that parental reading socialisation can facilitate students’ literacy development. However, the use of materials in Bidayuh as a native language as opposed to Malay or English may increase the rural parents’ participation in home-literacy activities, and encourage early literacy in children.